Greenwashing in the field of European Union law: environmental propaganda in fashion industry - Ruģēna, Ance Ilva (Riga Graduate School of Law, 2023)
In this bachelor thesis, the main focus is on examining whether the current European Union tools are effective enough in tackling greenwashing in the fashion industry. This thesis aims to emphasise the importance of rules regulating transparency and truthfulness in the fashion industry by reducing the use of greenwashing. The research is conducted by explaining definitions of the terms covering the scope of this thesis. Followed by an analysis of the decision-making process and an assessment of the legal tools currently in use. And finalised with case study examples, that emphasize how theoretical aspects are manifested in practice. The results of the thesis illustrate that the current tools used to combat greenwashing in the fashion industry are effective to an extent since additional developments and improvements are proven to be beneficial during this research.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::Environmental law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; greenwashing; European Green Deal